Rhizophoraceae Mangrove Saplings Use Hypocotyl and Leaf Water Storage Capacity to Cope with Soil Water Salinity Changes - Lechthaler, Silvia; Robert, Elisabeth M. R.; Tonné, Nathalie; Prusova, Alena; Gerkema, Edo; Van As, Henk; Koedam, Nico; Windt, Carel W. (Frontiers in Plant Science, 2016)
Some of the most striking features of Rhizophoraceae mangrove saplings are their voluminous cylinder-shaped hypocotyls and thickened leaves. The hypocotyls are known to serve as floats during seed dispersal (hydrochory) and store nutrients that allow the seedling to root and settle. In this study we investigate to what degree the hypocotyls and leaves can serve as water reservoirs once seedlings have settled, helping the plant to buffer the rapid water potential changes that are typical for the mangrove environment. We exposed saplings of two Rhizophoraceae species to three levels of salinity (15, 30 and 0-5 ‰, in that sequence) while non-invasively monitoring changes in hypocotyl and leaf water content by means of mobile NMR sensors. As a proxy for water content, changes in hypocotyl diameter and leaf thickness were monitored by means of dendrometers. Hypocotyl diameter variations were also monitored in the field on a Rhizophora species. The saplings were able to buffer rapid rhizosphere salinity changes using water stored in hypocotyls and leaves, but the largest water storage capacity was found in the leaves. We conclude that in Rhizophora and Bruguiera the hypocotyl offers the bulk of water buffering capacity during the dispersal phase and directly after settlement when only few leaves are present. As saplings develop more leaves, the significance of the leaves as a water storage organ becomes larger than that of the hypocotyl.